The effects of culturally relevant early childhood development (ECD) on gender relations and women empowerment - Zaki, Heba Mahmoud (AUC Knowledge Fountain, 2013)
Early Childhood Development has a significant impact on populations and societies. It contributes to the social transformation of communities, affecting both children and adults. Grassroots movements enabling community membersâ participation in such programs are replicable successful models for societal change. Early childhood developmentâ s multiple components of health, nutrition and hygiene affect child rearing practices of parents and various community members who are usually reached through the programâ s parental courses, training and community meetings. Early childhood development culturally appropriate, comprehensive programs have an impact on women that is hardly recognized. It contributes to participating womenâ s knowledge, awareness and empowerment. This study is concerned with the effect of culturally appropriate early childhood development on women empowerment and gender relations. The study adopts a qualitative research approach where data were collected through focus group discussions, interviews, observations and case studies. Findings of the study indicate a significant impact of early childhood education on women empowerment and gender relations. Furthermore, findings show that the success of the program heavily relied on its cultural contextualization, engagement and collaboration of community members.